Hormonal Imbalance? Balancing Free Trade and the Need for SPS Measures after the Decision in Hormones - Sandford, Iain (Victoria University of Wellington Law Review, 1999)
The Agreement on the Application of Sanitary and Phytosanitary Measures was negotiated during the Uruguay Round of multilateral trade negotiations to ensure that measures taken to protect humans and animals from foodborne risks, and to protect plants, animals and people from the risks of pests and diseases (SPS measures) were imposed only where they were justified. As such, the Agreement implicitly struck a balance between the freedom of World Trade Organization (WTO) Members to impose such legitimate measures and the objective of minimising trade disruptions. This article explores how this implicit balance was tested in the first SPS case to come before the WTO's new dispute settlement system European Communities Measures Concerning Meat and Meat Products (Hormones). This article examines the reasoning of both the Panel and Appellate Body considering the case and concludes that the final decision of the Appellate Body moved the balance too far in favour of Members' right to impose trade restrictive SPS measures.